1999
DOI: 10.1046/j.1365-2168.1999.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional endoanal sonography in assessing anal canal injury

Abstract: Multiplanar imaging has revealed a direct relationship between the length of a sphincter tear and its radial extent as shown on axial scanning. Marked sex differences in sphincter configuration have been demonstrated. In women the shorter anterior sphincter length highlights the risk of complete sphincter disruption with extensive tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
3
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(84 citation statements)
references
References 20 publications
6
68
3
7
Order By: Relevance
“…2,3 Further introduction of three-dimensional (3D) volume imaging has enabled accurate diagnostic evaluation of the full extent of the anal sphincter defect. 4 However, some patients find EAU embarrassing, the equipment is not universally available, and it requires a trained operator. Furthermore, the internal probe may cause disruption of the normal anatomy of the anal sphincter.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Further introduction of three-dimensional (3D) volume imaging has enabled accurate diagnostic evaluation of the full extent of the anal sphincter defect. 4 However, some patients find EAU embarrassing, the equipment is not universally available, and it requires a trained operator. Furthermore, the internal probe may cause disruption of the normal anatomy of the anal sphincter.…”
Section: Introductionmentioning
confidence: 99%
“…Outros estudos relataram que o comprimento do canal anal variou entre 3,27 e 3,4 cm, em homens e entre 2,52 e 2,93 cm, nas mulheres. [28][29][30][31] Esses dados justificaram os resultados que encontramos em pesquisa anterior, em que a eficĂĄcia da citologia anal foi superior quando as amostras foram obtidas atĂ© quatro cm, quando comparadas Ă s conseguidas em 2 cm. 22 Em relação ao tipo de coleta, atualmente dispomos do mĂ©todo do Papanicolaou, em que as amostras sĂŁo colhidas com escova (cytobrush) e o mĂ©todo da coleta Ășmida, o Thin Prep, em que a escova vem acondicionada em meio lĂ­quido e retorna a esse apĂłs seu uso.…”
Section: Discussionunclassified
“…However, at older ages, ES muscle could be thinner [16] . Recently, some studies found that 3D-ERUS could provide more information on the anal sphincters than traditional 2D-ERUS and might be able to measure sphincter accurately to predict the presence of ES atrophy [17] . The anterior ES of female is much shorter than that of the male, and this normal anatomical characteristic may be confused with an ES defect.…”
Section: Faecal Incontinencementioning
confidence: 99%